ELECTRODEPOSITION OF METALLIC MOLYBDENUM FROM AQUEOUS ELECTROLYTES CONTAINING HYDROFLUORIC ACID - Ivanova, Natalia; Ivanov, Sergey; Boldyrev, Evgen; Stadnik, Olga (Proceedings of National Aviation University (archive), 2006)
The influence of hydrofluoric acid on the cathodic reduction of molybdate ions has been investigated. It is shown that the mechanism of the process is determined by the acid concentration: in the range of concentrations less than 25 g·l–1 black or colored deposits are formed on the cathodic intermediate products of reduction of the molybdate ions the average valency of molybdenum in which is 3.6–4. At concentrations higher than 50 g·l–1 molybdate ions are completely reduced, forming on the cathode dense lustrous metal coatings 3–5 mm of thickness with good adhesion to the substrate. Addition of hydrofluoric acid prevents polymerization of molybdate ions. On the basis of Arrhenius equations, the effective activation energy of electroreduction of molybdate ions is determined, the ion size predetermining diffusion limitations of the processes proceeding at the film formed on the electrode surface.